Trophic ecology of Patagonian flounder Paralichthys patagonicus (Jordan, 1889) in the Argentine-Uruguayan Coastal Ecosystem - Troccoli, Gonzalo; Milessi, Andrés; Marí, Noemí; Figueroa, Daniel; De Wysiecki, Agustin (Instituto Nacional de Investigación y Desarrollo Pesquero, 2022)
Food habits and diet composition of Patagonian flounder Paralichthys patagonicus(Jordan, 1889) were studied on the basis of stomach content analyses from 828 specimens (512females, 304 males, 12 unsexed) collected during 16 commercial cruises between February 2009 andApril 2010 in the Argentine-Uruguayan Coastal Ecosystem (34° S-41° S). A total of 272 stomachs(32.9%) contained food (184 females and 84 males), among which 20 prey taxa were identified. Themost important prey category was pelagic fish, primarily Argentine anchovy (Engraulis anchoita),followed by rough scad (Trachurus lathami). Evidence showed that females consumed a higher totalwet weight of prey compared to males. Results also suggested a specialised diet over E. anchoita,across all sex and size groups. The estimated trophic level for the population of P. patagonicuswas4.16. This study suggests that P. patagonicusis a tertiary piscivorous consumer of the trophic foodweb in the region, and reveals changes in the prey consumption compared with previous studies.